A Readership Study Of An Agricultural Outlook Insert In A Farm Newspaper - John M. Sperbeck (Journal of Applied Communications, 1992)
A sample of 78 subscribers to a weekly agricultural newspaper was surveyed by telephone to determine readership and usefulness of an Ag Outlook insert.